Improving hydrodynamic efficiency of composite marine propellers in off-design conditions using shape memory alloy composite actuators. (15th November 2018) - Kapuria, S.; Das, H.N.
Abstract: The bend-twist coupling of fibre-reinforced composite laminates has been studied extensively to introduce self-adjustment in pitch angle of marine propellers for improving the hydrodynamic efficiency in off-design conditions. A recent study has shown that for full-scale propellers designed against material failure, the twist generated in the deformed blade due to this effect is not sufficient to cause any noticeable change in the hydrodynamic efficiency. In this paper, we study the use of shape memory alloy (SMA) for inducing variable twist in composite propellers for achieving the same. Prestrained SMA fibres are embedded in the composite in the martensite phase. When SMA fibres are heated upto the austenite phase, a large recovery stress is developed due to the shape memory effect. This stress is used to create twist in the propeller blade through appropriate positioning of the SMA actuators. A full-scale propeller of 4.2 m diameter, made of graphite epoxy with Nitinol fibres as SMA, is considered. The study establishes for the first time that using SMA composite actuator elements, it is possible to generate sufficient twist that can cause the desired improvement in the hydrodynamic performance of full-scale marine propellers at off-design conditions over a wide range of advance ratio. Highlights: Shape memory alloy (SMA) hybrid composite used for the first time to generate variable twist in full-scale marine composite propellers. Study considers viscous turbulent flow, and shear deformation effect, geometric nonlinearity and the material failure check of composite propeller blade. Thermomechanical behaviour of the SMA fibres predicted using the Brinson model. Twist control through temperature change of SMA wires illustrated. Results show the desired improvement in hydrodynamic efficiency of marine propellers at off-design conditions over a wide range of advance ratio.